PD-1 combined with TRBC1 and pan-T cell antibodies for robustly monitoring angioimmunoblastic T-cell lymphoma - Wang, Chunyan; Zhu, Li; Liu, Songya; Yi, Shujuan; Xiao, Min; Zhang, Yicheng; Mao, Xia (Frontiers in Medicine, 2022)
Background The diagnosis of AITL is challenging. It may be delayed or even missed due to critical clinical conditions and its histologic and immunophenotypic overlap with other neoplastic and reactive lymphoid proliferations. Objective The key objective is to obtain an efficient diagnosis, sensitive disease monitoring and treatment efficacy assessment of AITL using multiparameter flow cytometry (MFC). Methods In total, 167 de novo AITL patients were immunophenotypically profiled using sensitive MFC. We precisely identified the aberrant T-cell populations of AITL and performed an in-depth description of their phenotypic characteristics in comparison with their residual normal CD4+ T cells. A comparison of PD-1 expression was performed among AITL and other T-cell lymphomas. Results MFC detected a neoplastic T-cell population in 94.1% (80/85) of tissue, 71.5% (108/151) of bone marrow (BM), 100% (8/8) of peripheral blood (PB) and 78.6% (11/14) of body fluid samples. The most frequent immunophenotypic aberrations included the absence and diminished expression of CD3 (71.25% in tissues, 71.3% in BM, 75% in PB, 81.8% in hydrothorax and ascites specimens), followed by the loss or partial loss of CD7 (71.25% in LN, 67.6% in BM, 50% in PB, 81.8% in hydrothorax and ascites specimens). The immunophenotyping of neoplastic T-cell populations showed a high degree of similarity among different sites of the same patient and they might change over time but were relatively stable. Bright PD-1 expression showed high sensitivity and speciﬁcity in differentiating AITL from other T-cell lymphomas. In 14 AITL patients, neoplastic T-cell populations were initially missed by T-cell screening tube but were successfully discovered by bright PD-1 expression. Conclusion T-cell screening tube can reliably screen neoplastic T-cell populations in AITL patients with typical immunophenotyping, such as loss of surface CD3 and loss of CD7 with a relatively high ratio. Bright PD-1 expression is essential for identifying aberrant T cells in almost all AITLs. The clonality assessment antibody TRBC1 is efficient for robustly and cheaply assessing T-cell clonality. Using PD-1 and TRBC1 combined with pan-T antibodies can make a precise diagnosis of AITL and also sensitively monitor minimal residual disease regardless of the antigenic drift of the neoplastic T cells.